Soluble epoxide hydrolase gene deletion improves blood flow and reduces infarct size after cerebral ischemia in reproductively senescent female mice - Zuloaga, Kristen L.; Zhang, Wenri; Roese, Natalie E.; Alkayed, Nabil J. (Frontiers in Pharmacology, 2015)
Soluble epoxide hydrolase (sEH), a key enzyme in the metabolism of vasodilatory epoxyeicosatrienoic acids (EETs), is sexually dimorphic, suppressed by estrogen, and contributes to underlying sex differences in cerebral blood flow and injury after cerebral ischemia. We tested the hypothesis that sEH inhibition or gene deletion in reproductively senescent (RS) female mice would increase cerebral perfusion and decrease infarct size following stroke. RS (15-18 month old) and young (3-4 month old) female sEH knockout (sEHKO) mice and wild type (WT) mice were subjected to 45 min middle cerebral artery occlusion (MCAO) with laser Doppler perfusion monitoring. WT mice were treated with vehicle or a sEH inhibitor t-AUCB at the time of reperfusion and every 24hrs thereafter for 3 days. Differences in regional cerebral blood flow were measured in vivo using optical microangiography. Infarct size was measured 3 days after reperfusion. Infarct size and cerebral perfusion 24h after MCAO were not altered by age. Both sEH gene deletion and sEH inhibition increased cortical perfusion 24h after MCAO. Neither sEH gene deletion nor sEH inhibition reduced infarct size in young mice. However, sEH gene deletion, but not sEH inhibition of the hydrolase domain of the enzyme, decreased infarct size in RS mice. Results of these studies show that sEH gene deletion and sEH inhibition enhance cortical perfusion following MCAO and sEH gene deletion reduces damage after ischemia in RS female mice; however this neuroprotection in absent is young mice.